The characteristics of a two-dimensional supersonic sail - Boyd, E. A. (College of Aeronautics, 1960)
The two-dimensional supersonic sail is analysed using Busemann's second-order theory. It is found to have a universal shape, which is part of a Sici spiral. Aerodynamic characteristics are calculated for a few sails. The tension in sails flying at Mach numbers of 2 and 3 at altitudes of 20,000 and 70,000 feet is large and suggests that wire sails will be needed for flight under these conditions.